Che Guevara a revolutionary life - Anderson, Jon Lee 1957- (Grove Press, 2010)
Making use of unprecedented access to Guevara's personal archives, his guerrilla cohorts, and Cuban government archives, an exhaustive biography traces the life of the Latin American communist revolutionary
Keywords: Guevara, Che / 1928-1967; Guevara, Ernesto C.; Guevara, Che -- 1928-1967; Guerrillas / Latin America / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Political; HISTORY / Latin America / Central America; Guerrillas; Latin America; Biografie